PENGARUH MODEL PROBLEM BASED LEARNING BERBASIS TPACK TERHADAP HASIL BELAJAR IPAS KELAS III SD NEGERI LAWEYAN SURAKARTA TAHUN PELAJARAN 2024/2025 - Zakiyya Putri Salsabiilah; Oktiana Handini; Ani Restuningsih (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The purpose of this study was to determine the influence of the PBL model based on TPACK on IPAS learning outcomes in class III of SDN Laweyan Surakarta in 2024/2025 academic year. This research was conducted at SDN Laweyan Surakarta. The subjects were 27 third-grade students. This was a quantitative study with a non-equivalent control group design. This design had a treatment group and a control group. In this study, the researcher used data collection techniques such as tests, documentation, observation, and interviews. Based on the research results, the pretest mean score was 69.26 and the posttest mean score was 84.44. The significance data (2-tailed) showed that the value was 0.000 <0.05. This indicated that there is a difference between the pretest and posttest. The t-test obtained t-count was 13,000>t-table 2.055. Therefore, it can be concluded that the implementation of the TPACK-based PBL model has an influence on improving learning outcomes in the subject of IPAS in grade III of SDN Laweyan Surakarta in 2024/2025 academic year.